Quizizz As Game-Based Learning In English Classes: Lecturer’s And Students’ Perception - Yulianti Yulianti; Muhammad Basri Jafar; La Sunra La Sunra (State University of Makassar, 2023)
This study aims to determine the lecturer’s and students’ perceptions of Quizizz. The researcher analysed the data using the descriptive qualitative method. The researcher used interviews as qualitative research instruments. The participants in this research were one lecturer and seven students in English class at the Islamic State University of Alauddin Makassar. The results showed that the perception of the lecturer based on the experience is the lecturer used Quizizz only for reviewing material and the students were included in the high and moderate categories of perceptions based on feelings, thinking ability, and experience. Keywords– Implementation, Quizizz, game-based learning, English classes